Nutritional safety and suitability of a specific protein hydrolysate derived from whey protein concentrate and used in an infant and follow‐on formula manufactured from hydrolysed protein by HIPP‐Werk Georg Hipp OHG (dossier submitted by meyer.science GmbH). (9th March 2022) - ,; Bohn, Torsten; Castenmiller, Jacqueline; de Henauw, Stefaan; Hirsch‐Ernst, Karen‐Ildico; Katrine Knutsen, Helle; Maciuk, Alexandre; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Pelaez, Carmen; Pentieva, Kristina; et al.
Abstract: The European Commission asked EFSA to deliver an opinion on the nutritional safety and suitability of a specific protein hydrolysate. It is derived from whey protein concentrate and used in infant and follow‐on formula by HIPP‐Werk Georg Hipp OHG. The dossier that was submitted to the European Commission aimed at requesting an amendment of Regulation (EU) 2016/127 with respect to the protein sources that may be used in infant and/or follow‐on formula. This opinion does not cover the assessment of the safety of the food enzymes used in the manufacture of the protein hydrolysate. The protein hydrolysate under evaluation is sufficiently characterised with respect to the fraction of the hydrolysed protein. In the pertinent intervention study provided, an infant formula manufactured from the protein hydrolysate with a protein content of 1.9 g/100 kcal and consumed as the sole source of nutrition by infants for 3 months led to growth equivalent to a formula manufactured from intact cow's milk protein with the same protein content. No experimental data have been provided on the nutritional safety and suitability of this protein source in follow‐on formula. However, given that it is consumed with complementary foods and the protein source is considered nutritionally safe and suitable in an infant formula that is the sole source of nutrition of infants, the Panel considers that the protein hydrolysate is also a nutritionally safe and suitable protein source for use in follow‐on formula. The Panel concludes that the protein hydrolysate under evaluation is a nutritionally safe and suitable protein source for use in infant and follow‐on formula, as long as the formula in which it is used contains a minimum of 1.9 g/100 kcal protein and complies with the compositional criteria of Commission Delegated Regulation (EU) 2016/127 and the amino acid pattern in its Annex IIIA.